Simulasi Keamanan Jaringan Dengan Metode DHCP Snooping Dan VLAN Mengggunakan CISCO - Brian Rinanto Saputra (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Computer networks have a weakness because network access is only provided through a DHCP server. The consequence of this is the occurrence of DHCP Rogue which is a fake server that gives the wrong gateway address to the client computer so that the computer cannot connect to the network and the internet. with DHCP snooping it is hoped that it can help internet network security because access to the IP address or MAC address that has been registered on the router and attackers cannot enter the network. The research method uses Cisco Packet Tracer 8.0 software with a topology of 2 routers. The implementation results show that DHCP Snooping can limit unapproved or unknown DHCP Servers to provide malicious information to clients so that it can help better security